2022
DOI: 10.3390/ijerph19159023
|View full text |Cite
|
Sign up to set email alerts
|

Do Personality, Alcohol Abstinence Self-Efficacy, and Depressive Symptomatology Affect Abstinence Status in Treatment-Seeking Patients with Alcohol Use Disorder?

Abstract: Given the high global incidence and disabling nature of alcohol use disorders, alongside high relapse rates, we sought to investigate potential predictors of abstinence, considered a prerequisite of full remission. With an aim to examine (i) the effect of personality, alcohol abstinence self-efficacy, and depressive symptomatology on abstinence status as our primary objective, and (ii) interactions between these three factors, as well as (iii) their changes over time as two secondary objectives, we recruited 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…단주자 기효능감은 알코올 소비를 최소화하거나 중단하고, 갈망 과 유혹에 저항하며 음주 행동의 변화를 유지할 수 있는 자신의 능력에 대한 자신감으로서 음주와 관련된 문제에 영향을 미치는 것으로 보고되어 왔다 [13]. 알코올 사용장 애(alcohol use disorder, AUD)의 치료에 있어 재발한 사람에 비해 단주한 사람의 자기효능감이 더 높은 것으로 나타나며 [14,15]…”
Section: 서 론unclassified
“…단주자 기효능감은 알코올 소비를 최소화하거나 중단하고, 갈망 과 유혹에 저항하며 음주 행동의 변화를 유지할 수 있는 자신의 능력에 대한 자신감으로서 음주와 관련된 문제에 영향을 미치는 것으로 보고되어 왔다 [13]. 알코올 사용장 애(alcohol use disorder, AUD)의 치료에 있어 재발한 사람에 비해 단주한 사람의 자기효능감이 더 높은 것으로 나타나며 [14,15]…”
Section: 서 론unclassified
“…Rehabilitation centers are focused on promoting abstinence and preventing further harm. During the withdrawal of alcohol, alcohol abstinence self-efficacy affects the subjective wellbeing of the alcohol drinkers undergoing treatment for alcohol dependence syndrome [6]. It has been observed that there were changes in the social well-being and demeanor of the individuals during the withdrawal of alcohol [7].…”
Section: Introductionmentioning
confidence: 99%